Incidence of histological prostatitis and its correlation with PSA density - Affonso Celso Piovesan (Clinics, 2009)
OBJECTIVE: The aim of this study was to determine the incidence of asymptomatic, histologically proven prostatitis in men with symptoms of benign prostate hyperplasia and to observe the correlation between asymptomatic prostatitis and prostate specific antigen (PSA) density. INTRODUCTION: The incidence of type IV prostatitis is unknown. There is a tendency to correlate the presence of inflammatory prostatitis with an elevation of PSA. MATERIALS AND METHODS: From August 2000 to January 2006, 183 patients who underwent surgical treatment for benign prostate hyperplasia as a result of obstructive or irritative symptoms were prospectively studied. In accordance with the histology findings, these patients were divided into two groups: group I included patients with the presence of histological prostatitis and group II included patients with the absence of histological prostatitis. The mean PSA densities were compared. RESULTS: Histological evidence of prostatitis was observed in 145 patients. In this group, the mean PSA density was 0.136 ± 0.095. In 38 cases, there was no evidence of inflammation upon histological examination of the surgical samples. In these 38 cases, the mean PSA density was 0.126 ± 0.129. No statistically significant differences were detected between the two groups; the p-value is 0.124. CONCLUSION: Abnormal PSA density should not be attributed to the inflammatory prostatitis process.